Postmastectomy Breast Reconstruction in Patients with Non-Metastatic Breast Cancer: An Ontario Health (Cancer Care Ontario) Clinical Practice Guideline - Toni Zhong; Glenn G. Fletcher; Muriel Brackstone; Simon G. Frank; Renee Hanrahan; Vivian Miragias; Christiaan Stevens; Danny Vesprini; Alyssa Vito; Frances C. Wright (Current Oncology, 2025)
Several postmastectomy breast reconstruction techniques and procedures have been implemented, although with limited evaluation of benefits and adverse effects. We conducted a systematic review on the plane and timing of reconstruction, and on the use of nipple-sparing mastectomy, acellular dermal matrix, and autologous fat grafting as the evidence base for an updated clinical practice guideline on breast reconstruction for Ontario Health (Cancer Care Ontario). Both immediate and delayed reconstruction may be considered, with preferred timing depending on factors such as patient preferences, type of mastectomy, skin perfusion, comorbidities, pre-mastectomy breast size, and desired reconstructive breast size. Immediate reconstruction may provide greater psychological or quality of life benefits. In patients who are candidates for skin-sparing mastectomy and without clinical, radiological, and pathological indications of nipple-areolar complex involvement, nipple-sparing mastectomy is recommended provided it is technically feasible and acceptable aesthetic results can be achieved. Surgical factors including incision location are important to reduce necrosis by preserving blood supply and to minimize nerve damage. There is a role for both prepectoral and subpectoral implants; risks and benefits will vary, and decisions should be made during consultation between the patient and surgeons. In patients who are suitable candidates for implant reconstruction and have adequate mastectomy flap thickness and vascularity, prepectoral implants should be considered. Acellular dermal matrix (ADM) has led to an increased use of prepectoral reconstruction. ADM should not be used in case of poor mastectomy flap perfusion/ischemia that would otherwise be considered unsuitable for prepectoral reconstruction. Care should be taken in the selection and handling of acellular dermal matrix (ADM) to minimize risks of infection and seroma. Limited data from small studies suggest that prepectoral reconstruction without ADM may be feasible in some patients. Autologous fat grafting is recommended as a treatment for contour irregularities, rippling following implant-based reconstruction, and to improve tissue quality of the mastectomy flap after radiotherapy.